Constitutionality of Constitutional Developments as an Important Prerequisite for Stable Democracy - Manasyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2018)
The issues regarding the idea of “constitutionality of constitutional developments” are discussed in the article. The Author substantiates that notwithstanding the first paradoxical impression of the discussed notion, the latter is one of the most important elements for guaranteeing constitutionalism, has concrete content and important role in ensuring stable democracy.